The Effect of the Internal Control System, the Competency of Village Employees and Organizational Commitments on Village Physical Development in Galang District Deli Serdang Regency - Vini Dwi Putranti; Badaruddin Badaruddin; Sirojuzilam Sirojuzilam (Budapest International Research and Critics University, 2021)
The objectives of this study are to: 1) Analyze the effect of the internal control system on the physical development of villages in Galang District, Deli Serdang Regency; 2) Analyzing the influence of village apparatus competence on village physical development in Galang District, Deli Serdang Regency and 3) Analyzing the effect of organizational commitment on village physical development in Galang District, Deli Serdang Regency. The research was conducted in Galang District concerning the Effect of Internal Control Systems, Village Apparatus Competence and Organizational Commitment on Village Physical Development in Galang District, Deli Serdang Regency. The method of analysis used in this research is multiple regression analysis. The results showed that the internal control system has a positive and significant effect on the physical development of the village in Galang District, Deli Serdang Regency. The competence of village officials has a positive and significant effect on the physical development of the village in Galang District, Deli Serdang Regency. Organizational commitment has a positive and significant effect on the physical development of villages in Galang District, Deli Serdang Regency.